Cutaneous Sensory Block Area, Muscle-Relaxing Effect, and Block Duration of the Transversus Abdominis Plane Block. Issue 4 (July 2015) - Støving, Kion; Rothe, Christian; Rosenstock, Charlotte V.; Aasvang, Eske K.; Lundstrøm, Lars H.; Lange, Kai H. W.
<x xml:space="preserve">Abstract</x> Background and Objectives The transversus abdominis plane (TAP) block is a widely used nerve block. However, basic block characteristics are poorly described. The purpose of this study was to assess the cutaneous sensory block area, muscle-relaxing effect, and block duration. Methods Sixteen healthy volunteers were randomized to receive an ultrasound-guided unilateral TAP block with 20 mL 7.5 mg/mL ropivacaine and placebo on the contralateral side. Measurements were performed at baseline and 90 minutes after performing the block. Cutaneous sensory block area was mapped and separated into a medial and lateral part by a vertical line through the anterior superior iliac spine. We measured muscle thickness of the 3 lateral abdominal muscle layers with ultrasound in the relaxed state and during maximal voluntary muscle contraction. The volunteers reported the duration of the sensory block and the abdominal muscle–relaxing effect. Results The lateral part of the cutaneous sensory block area was a median of 266 cm2 (interquartile range, 191–310 cm2) and the medial part 76 cm2 (interquartile range, 54–127 cm2). In all the volunteers, lateral wall muscle thickness decreased significantly by 9.2 mm (6.9–15.7 mm) during a maximal contraction. Sensory block and muscle-relaxing effect duration were 570 minutes (512–716 minutes) and 609 minutes (490–724 minutes), respectively. Conclusions Cutaneous sensory block area of the TAP block is predominantly located lateral to a vertical line through the anterior superior iliac spine. The distribution is nondermatomal and does not cross the midline. The muscle-relaxing effect is significant and consistent. The block duration is approximately 10 hours with large variation.